PO18 | Does muscle mass matter? Appendicular lean mass as a determinant of anti-XA activity in elderly patientes (Bleeding, Thrombosis and Vascular Biology, 2025)
Introduction: Direct oral anticoagulants (DOACs) are first-line treatments for venous thromboembolism (VTE) and stroke prevention in non-valvular atrial fibrillation (NVAF). Dosing is currently based on age, body weight, and glomerular filtration rate (GFR). However, aging alters body composition, notably reducing lean mass, which is not detectable by body weight and may affect DOAC pharmacokinetics. Aims: This study investigates whether appendicular lean mass (ALM) influences anti-Xa activity in older patients on DOACs, independently of age, sex, weight, and GFR.